Post mortem analysis of a tungsten coated tile from the outer divertor strike point region of ASDEX upgrade. (December 2016) - Fortuna-Zalesna, E.; Andrzejczuk, M.; Ciupinski, L.; Rozniatowski, K.; Sugiyama, K.; Mayer, M.; Kurzydlowski, K.J.; ,
Highlights: New data on materials mixing and plasma-induced damage of the tungsten coating. The changes in the morphology induced by two processes erosion and re-deposition. Thick deposit layers in the shadowed areas (foam like structures). Stratified deposits with crystals rich in boron in the private flux region. The tungsten layer kept its thickness even after three campaigns of AUG operation. Abstract: In the present study, the structure and the composition of co-deposited layers developed at the outer divertor strike point tile 1 in ASDEX Upgrade during three campaigns from 2009 to 2013 were examined. The samples were cut from representative locations which differed in received flux: private flux, strike point, the highest plasma fluence and "moderate" flux regions. High resolution scanning (SEM) and transmission electron microscopy (HRSTEM) combined with energy-dispersive X-ray spectroscopy (EDS) and optical profilometry have been used to identify deposits composition and morphology as well as to assess coating degradation. The aim of the post-mortem analyses was the evaluation of materials mixing and evidence of plasma-induced damage. Our results confirm that the outer divertor of AUG is generally a net erosion region for tungsten, however, the strong deposition of eroded tungsten takes place close to the outer strike point (private flux region). The observations on cross-sections of the tungsten coatings revealed micro-cracks around the strike point region. These cracks are caused by thermal stresses due to periodic heating and cooling of the layer during ELMs.